The Impact of the Euro Adoption on inside and outside Eurozone Trade - Chen, Ling-Yu (Archives of Business Research, 2019)
This study focuses on the differential trade effect between the Euro countries and non-euro countries within the 28 European Union (EU) countries. The study period is from 1999 to 2015. We use the panel data models to assess the differential trade effects of these two groups of countries. Our results show that compared to the non-euro-adopting EU countries, the euro-adopting EU countries will export 17.4 % more to the Eurozone. Besides, the euro-adopting countries export 11.6 % more to the non-Eurozone countries than the non-euro adopting EU countries do. In addition, we find that compared to the non-euro adopting EU countries, the euro-adopting EU countries would have a more stable exports, regardless inside or outside Eurozone trade. Our conclusion is that compared to those EU countries not adopting the euro, the euro adopting countries could have more exports, especially the exports to the common currency adoption area. In addition, compared to those non-euro adoption countries, the euro adopting countries can have more stabilized exports inside Eurozone. However, the differential export stabilizing effects do not different from alternative export destinations.